The Influence of Academic Supervision of Teachers by the Principal on the Improvement of Learning Outcomes - Yudi Harnano; Saryanto Saryanto; Jumintono Jumintono (CV. Edujavare Publishing, 2026)
Improving the quality of basic education is largely determined by the quality of the learning process taking place in the classroom. This study aims to analyze the influence of academic supervision of teachers by the principal on improving learning outcomes at Tlogomulyo Public Elementary School. The study used a quantitative approach with an ex post facto type. The study population was all teachers at Tlogomulyo Public Elementary School, with a saturated sampling technique so that the entire population became respondents. Data were collected through a questionnaire to measure the principal's academic supervision and documentation of learning outcomes as indicators of the dependent variable. Data were analyzed using simple linear regression after first undergoing validity, reliability, normality, and linearity tests. The results showed that academic supervision of teachers by the principal had a positive and significant effect on improving learning outcomes at Tlogomulyo Public Elementary School. Academic supervision implemented through planning, classroom observation, providing feedback, and follow-up coaching was able to improve teachers' pedagogical competence, improve the quality of the learning process, and encourage teachers to be more reflective and innovative in teaching. This improvement in the quality of learning has an impact on improving student learning outcomes, both in terms of activeness, understanding of the material, and academic achievement. Thus, academic supervision by the principal has proven to be an important factor in improving the quality of learning in elementary schools.